"Mexican, Not Latino": A T-shirt as an Artifact of Creative Subversion. Issue 1 (February 2019) - Puebla, César A. Cisneros
In this brief piece, I introduce "state terrorism" and "accumulation by dispossession" as a framework to represent Donald Trump as a specific personification of a large group of past and current presidents who have led or actually are leading some nations in a particular way. It is formulated as a demand to study the daily life using qualitative methodologies and create new ways of producing useful knowledge to actively transform our societies. A T-shirt is depicted as an artifact of creative subversion in the context of a permanent dialogue between Mexicans and Americans on public themes such as a wall on the border.